2020
DOI: 10.1111/jce.14814
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of pacing‐induced cardiomyopathy in pacemaker‐dependent patients is lower with leadless pacemakers compared to transvenous pacemakers

Abstract: Introduction Frequent right AQ4ventricular pacing (≥40%) with a transvenous pacemaker (TVP) is associated with the risk of pacing‐induced cardiomyopathy (PICM). Leadless pacemakers (LPs) have distinct physical and mechanical differences from TVP. The risk of PICM with LP is not known. To identify incidence, predictors, and long‐term outcomes of PICM in LP and TVP patients. Methods The study comprised all pacemaker‐dependent patients with LP or TVP who had left ventricular ejection fraction (LVEF) of ≥50 from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 19 publications
4
20
3
1
Order By: Relevance
“…13–15 Sanchez and colleagues recently reported a substantially lower rate of pacemaker-induced cardiomyopathy among a single-centre cohort of pacemaker-dependent patients receiving leadless VVI devices (3%) compared to those receiving transvenous pacemakers (13.7%). 16 Whether rates of device system revision in longer-term follow-up are different between leadless and transvenous VVI pacemakers is an important clinical question. After adjustment for baseline clinical risk, leadless VVI pacemakers were associated with a 38% lower rate of reintervention at 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…13–15 Sanchez and colleagues recently reported a substantially lower rate of pacemaker-induced cardiomyopathy among a single-centre cohort of pacemaker-dependent patients receiving leadless VVI devices (3%) compared to those receiving transvenous pacemakers (13.7%). 16 Whether rates of device system revision in longer-term follow-up are different between leadless and transvenous VVI pacemakers is an important clinical question. After adjustment for baseline clinical risk, leadless VVI pacemakers were associated with a 38% lower rate of reintervention at 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding causation, it is difficult to disentangle the role of mechanical disruption of tricuspid valve by pacemaker leads from pacing induced dyssynchrony, but it is plausible that both contribute. (Cheema et al, 2021 ; Khurshid et al, 2014 ; Lamas et al, 2000 ; Mandras & Desai, 2021 ; Matusik et al, 2010 ; Sanchez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that leadless pacemaker therapy resulted in worsening biventricular function and mitral regurgitation and had an equivalent rate of deterioration in tricuspid regurgitation compared to a transvenous pacemaker ( 15 ). Although one study including 198 patients with 100% right ventricular pacing reported a 3 vs. 14% incidence of pacing-induced cardiomyopathy (PICM) in leadless and transvenous pacemaker groups, larger studies are required to confirm the stated lower incidence of PICM in patients with leadless pacemakers ( 16 ). Surgical epicardial lead implantation or endocardial lead placement via trans-atrial access should be the last resort due to invasiveness.…”
Section: Discussionmentioning
confidence: 99%